Aktualisasi Nilai-Nilai Pancasila Sila Ke-1 Tentang Pengajaran Mengaji Kepada Anak-Anak Sekolah Dasar - Lestari Mardiana; Mohamad Irgi AlFauji; Muhamad Nastainu Billah; Muhammad Afif Zuliandi; Muhammad Dzaky Zainuri; Muhammad Ilyas Dermawan; Nabila Rizki Kamila; Nadya Rozathul Janah; Najma Annisa Syaefryan; Bobang Noorisnan Pelita; Dian Herdiana (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The intent and purpose of this program is to teach children to read the Qur'an properly and correctly and then memorize short letters from the start of the QS. Al-Kafirun to QS. An-Nas, especially children aged 6-12 years, namely elementary school age aged 1-6 years. Learning is realized in the area where we live. In this program, we evaluate participants' ability to memorize from various aspects, including the ability to read and memorize the Qur'an fluently and obey the rules of reading the Qur'an. The benefits that participants will get from this activity are as follows: Learning the Qur'an, especially memory, helps children's intelligence and receives rewards for their actions. The transformational activities carried out by students of UIN Sunan Gunung Djati Bandung can be described as follows: Reading and memorizing QS. Al-Kafirun – QS. An-Nas. Life guide to achieve happiness in this world and the hereafter